Penggunaan Bahasa Figuratif dalam Novel Kabut Pantai Anyer Karya Anny Djati W: Kajian Stilistika dan Implementasinya dalam Pembelajaran Sastra Di SMA - Rahmanto, Aris, Prof. Dr. Ali Imron Al Ma'ruf,M.Hum (2017)
The purpose of this study was to describe (1) the sosio-cultural of the outhor of the Kabut Pantai Anyer by Anny Djati W, (2) the structure of the Kabut Pantai Anyer novel by Anny Djati W, (3) the stylistic in it, and (4) the implementation of the results of the research work of the novel as literary materials in high school. The study used qualitative descriptive research. Data analysis techniques used in this research is the technique of dialectic. The results of the analysis can be summed up as follows. (1) The sosio-cultural background of author of the novel Kabut Pantai Anyer by Anny Djati W, (2) Based on the structuralism, the novel's theme is revenge for infidelity. The flow of the story is advanced flow (progressive). The setting is divided into three part: the time setting occurred between 2009. The place setting located in Jakarta and Banten. Social background in this novel take on a life of social background Atila familys coming from the upper middle class. (3) Used figurative language in the novel Kabut Pantai Anyer by Anny Djati W is style language, idiom, proverb. (4) The results of this research are implemented as literary materials in high school based on the SK 7 i.e. understand the various saga, Indonesian novel or translations and KD 7.2 i.e. analyze the intrinsic and extrinsic elements of Indonesian novels or translations. There the three important aspects that should not be overlooked when selecting teaching materials literature namely, (1) the angle of language, (2) the angle of psychology (mental maturity), (3) corner of the cultural background of learners.